Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast